TIME-MANAGEMENT AS AN EFFECTIVE MEANS OF MANAGING TIME FOR EDUCATION INSTITUTION EMPLOYEE - Tatiana E. Simina; Tatiana A. Zalygina (Вестник Российского экономического университета имени Г. В. Плеханова)
In today’s world private time is a key resource for any person, which often has even a higher value than money. Competent managing one’s time resource implies adequate assessment of the situation, making relevant decisions with due regard to time costs needed to attain the set goals, designing the program of reaching the goals in time space and strict control over time limits of the activity. Repeated non-fulfillment, delay or postponing of planned objectives (procrastination) could cause internal discomfort and even result in nervous and psychic disturbance and depression. The skill of using one’s time effectively and managing it with high quality is valuable for each person, especially for education institutions’ workers. The authors present findings of surveying lecturers concerning timemanagement and principles of its use in pedagogic work and everyday life. Questionnaires and analysis of pedagogic specialists’ work provide an opportunity to identify problems of managing work time and private time. As a result of this research the authors worked out recommendations aimed at effective use of time-management principles in the process of pedagogic activity.